1999
DOI: 10.1366/0003702991947568
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Methylene Blue and Sodium Dodecyl Sulfate in Aqueous Solution Studied by Molecular Spectroscopy

Abstract: The interactions of methylene blue (MB, a cationic redox indicator and biological stain) and sodium dodecyl sulfate (SDS, a micelle-forming, anionic surfactant) in aqueous solution have been examined by using Rayleigh scattering, UV-visible absorption, and fluorescence spectroscopy. At SDS concentrations significantly below the critical micelle concentration (cmc), MB forms noncovalent dimers and aggregates with SDS that scatter light but do not fluoresce. For solutions containing 1 μM MB and < 3–5 mM SDS, shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…26 Carroll et al demonstrated that the scattering signal from a 1 μM MB solution exhibits a strong signal for ½SDS ¼ 1.5 to 4.5 mM, suggesting the presence of a large aggregate in that range. 36 Those results indicate the formation of MB-SDS clusters or premicellar aggregates before the CMC is reached. We suggest that these premicelles are formed by strong electrostatic interactions between anionic SDS and cationic MB with the surfactant possibly intercalating its hydrophobic tail between adjacent MB molecules [ Fig.…”
Section: Dimerization In Sodium Dodecyl Sulfatementioning
confidence: 93%
See 2 more Smart Citations
“…26 Carroll et al demonstrated that the scattering signal from a 1 μM MB solution exhibits a strong signal for ½SDS ¼ 1.5 to 4.5 mM, suggesting the presence of a large aggregate in that range. 36 Those results indicate the formation of MB-SDS clusters or premicellar aggregates before the CMC is reached. We suggest that these premicelles are formed by strong electrostatic interactions between anionic SDS and cationic MB with the surfactant possibly intercalating its hydrophobic tail between adjacent MB molecules [ Fig.…”
Section: Dimerization In Sodium Dodecyl Sulfatementioning
confidence: 93%
“…During this stage, premicelles may be disaggregating with MB molecules released as MB/SDS quenched ion pairs. 7,36 Finally, at SDS concentrations greater than 7 mM, the triplet transient absorption increases logarithmically until reaching a plateau corresponding to full monomerization. Concurrently, the absorption maximum at 665 nm is blue-shifted compared to the monomer spectrum signifying that the monomers are surrounded by a more polar environment than in water without SDS (most likely the negatively charged surface of the micelle) [ Fig.…”
Section: Dimerization In Sodium Dodecyl Sulfatementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, several studies have found MB to have a significantly lower photoactivity when in the form of molecular aggregates [14,[26][27][28]. This phenomenon was generally interpreted in terms of a very rapid deactivation of excited molecules via non-radiative relaxation pathways.…”
Section: Methylene Blue Fluorescence Spectramentioning
confidence: 89%
“…It results in a decreasing of the fluorescence intensity and on the singlet oxygen formation [49]. These studies have shown that the interaction with micelles is responsible for the dimerization process and not the interaction with monomer of the surfactant, as it has been postulated in some works [ 169 ]. In this stage of the work it is important to study the nature of the aggregates formed in different negatives interfaces and in biological systems, more specifically in micelles, vesicles and mitochondria.…”
Section: Aggregation Of Photosensitizers and Its Influence In Pdtmentioning
confidence: 92%